MENGEMBANGKAN KEMAMPUAN MOTORIK HALUS ANAK MENGGUNAKAN MODEL PJBL, DIRECT INSTRUCTION, DAN MEDIA MAGIC LEARN BOX - Agustin, Nia Fransiska; Rini, Tika Puspita Widya (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
The problem in this study was the low development of children's fine motor skills. This issue was due to the lack of variation in teaching models and learning media, as well as limited activities involving hand-eye coordination. Children experienced difficulties in activities such as cutting, threading, and holding writing tools correctly. To overcome these problems, the researcher applied the Project Based Learning model, Direct Instruction method, and Magic Learn Box media. The purpose of this study was to describe teacher activities, children’s learning activities, and the improvement in children's fine motor skills. This research used a qualitative approach with the Classroom Action Research (CAR) method, conducted over four sessions. The subjects were 11 children in Group A at TK Sun Shine Banjarmasin Utara. Instruments included observation sheets for teacher activities, student activities, and fine motor skill achievement. Data were collected through observation and documentation. The results showed a significant improvement. Teacher activity increased steadily, reaching the